The nexus between teacher education and Africa’s development - Matunhu, Jephias (University Coast of Ghana, 2016)
The 56th Yearbook on Teacher Education is a collection of papers and reports from the 56th World Assembly held on the 10-12 July 2012, at the University of Cape Coast, Ghana